DESIGN ANALYSIS OF CYLINDRICAL FLOAT TYPE WAVE EVERGY CONVERTER - Dhipta Rama Samodra; Mohammad Hakam; Agung Purwana (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
The potential of the sea in Indonesia is commonly used for the utilization of renewable energy from sea waves. One of the efforts to utilize energy, among others, is using a power plant by utilizing seawater wave power energy. So there is a need for ideas and design concepts about mechanical transmission of power plants powered by more effective seawater waves. This study aims to analyze the design of a cylindrical float type Marine Wave Power Plant (PLTG). This discussion focuses on variations in the height of a device, arm length, and buoy diameter. Where when the amplitude and frequency of water waves provide up and down movements of the cylindrical buoy. Then the torque will be generated from the main shaft which has a one way bearing which aims to rotate in the same direction, then forwarded to rotate the generator which will produce electrical energy. The largest power value is obtained in the variation of tool height (Y = 0.5 m), arm length (Pl = 3 meters), and diameter (ø = 0.4 m) which is 599.596 watts. Then the smallest power value in the variation of tool height (Y = 1.5 m), arm length (Pl = 2 m) and buoy diameter (ø = 0.6 m) which is 291.334 watts.